2001
DOI: 10.1128/jb.183.22.6721-6725.2001
|View full text |Cite
|
Sign up to set email alerts
|

Colicin A Immunity Protein Interacts with the Hydrophobic Helical Hairpin of the Colicin A Channel Domain in the Escherichia coli Inner Membrane

Abstract: The colicin A pore-forming domain (pfColA) was fused to a bacterial signal peptide (sp-pfColA). This was inserted into the Escherichia coli inner membrane in functional form and could be coimmunoprecipitated with epitope-tagged immunity protein (EpCai). We constructed a series of fusion proteins in which various numbers of sp-pfColA ␣-helices were fused to alkaline phosphatase (AP). We showed that a fusion protein made up of the hydrophobic ␣-helices 8 and 9 of sp-pfColA fused to AP was specifically coimmunopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Using a coimmunoprecipitation procedure, Espesset et al showed that there is an interaction between the colicin A pore-forming domain bound to the cytoplasmic membrane and its immunity protein (189). This interaction did not require the channel to be in the open state but required the presence of the hydrophobic helical hairpin in the membrane (189,477), indicating that A-type immunity proteins can bind colicins prior to pore formation. In the E1-type colicin, the situation seems to be more complex, since the transmembrane helices recognized by the immunity protein are located in the voltage-gated region of the colicin.…”
Section: Pore-forming Colicinsmentioning
confidence: 99%
“…Using a coimmunoprecipitation procedure, Espesset et al showed that there is an interaction between the colicin A pore-forming domain bound to the cytoplasmic membrane and its immunity protein (189). This interaction did not require the channel to be in the open state but required the presence of the hydrophobic helical hairpin in the membrane (189,477), indicating that A-type immunity proteins can bind colicins prior to pore formation. In the E1-type colicin, the situation seems to be more complex, since the transmembrane helices recognized by the immunity protein are located in the voltage-gated region of the colicin.…”
Section: Pore-forming Colicinsmentioning
confidence: 99%
“…Asterisks indicate conserved amino acids within the colicin proteins. Underlined amino acid sequence represent the 10 known alpha-helices as determined for ColA (27). Helices 8 and 9 are shown in grey.…”
Section: Vol 47 2003mentioning
confidence: 99%
“…Helices 8 and 9 are shown in grey. colicin molecule to a specific outer membrane receptor protein, the N-terminal domain mediates translocation through the cell envelope, and the C-terminal domain exerts the lethal effect (27,30).…”
Section: Vol 47 2003mentioning
confidence: 99%
“…The first biochemical evidence of pore-forming colicin physically interacting with its immunity protein was reported by Espesset et al (1996), who showed that a colicin A poreforming domain, fused to a prokaryotic signal peptide (sppfColA), could be co-immunoprecipitated with its cognate epitope-tagged immunity protein (EpCai) (17). Using the same co-immunoprecipitation procedure, Nardi et al demonstrated that the smallest fragment of colicin A recognized by Cai was the hydrophobic helical hairpin (18).…”
mentioning
confidence: 99%